Downtime cost analysis of offloading operations due to influence of partially standing waves in Malaysian waters and development of graphical user interface - Patel, M.S.; Khalifa, A.A.; Liew, M.S.; Mustaffa, Z.; Whyte, Andrew (SPRINGER, 2020)
© 2020, Springer Science+Business Media, LLC, part of Springer Nature.